A influência do uso do sistema de controle gerencial na cultura de inovação: um estudo em pequenas e médias empresas do setor contábil - Bicicgo, Juliano (2021)
In the search for competitive advantage, the Management Control System (MCS) and innovation have proven to be relevant in the business sphere. Management controls started to be seen as mere bureaucratic instruments for agents of organizational transformation, capable of guiding aspects relevant to innovation, intervening in culture, guiding it through the structuring of the innovative process. In the national literature, there are few studies focusing on understanding this relationship in the service sector. Thus, the general objective is to analyze the influence of the MCS in the Levers of Control (LOC) model by Simons (1995) on the culture of innovation in small and medium-sized companies in the accounting sector. Data collected through a survey with 254 respondents from 14 states in the national territory were analyzed using correlation analysis and multiple linear regression. The findings support the hypothesis that levers that are encouraging, interactive control and beliefs, influence the culture of innovation. These results indicate how organizations can act through the implementation and consolidation of interactive and belief control systems, intending to foster a favorable context for innovation. In addition, this study contributes to the advancement of knowledge in the areas of control and innovation.